Can carbon taxes and subsidies promote both carbon reduction and economic growth in dairy farming?—A case study from the global golden milk source belt - Shi, Shuai; Liu, Changyu; Chi, Jia; Jing, Yu; Wang, Xiaochen (Frontiers in Sustainable Food Systems, 2025)
Dairy farming (DF) is a significant source of carbon emissions (CEs) in animal husbandry. How to use taxation and subsidies to promote carbon emission reduction while ensuring industrial economic growth has become a focus of academic attention. This study uses a market equilibrium model to explore the impact of carbon emission tax (CET) and subsidies on carbon abatement and economic growth in dairy farming. It sets up different scenarios to find a win–win ratio between tax and subsidy. The empirical test was carried out in Heilongjiang Province in the global golden milk source belt. The results show that the scenarios significantly suppressed CEs. However, carbon taxes led to a decrease in milk yield, while subsidies led to an increase. If the subsidies are <92% of tax revenue, there is a decrease in milk yield. When the carbon tax revenue is equivalent to the subsidies, a reduction in emissions of 0.02–0.11% can be achieved, accompanied by an increase in milk yield ranging from 0.032% to 0.160%. When the subsidy-to-tax ratio ranges from 1.311 to 2.045, dairy yield growth is most closely aligned with emissions, enabling the government to make decisions based on different policy targets.